The intersection of disability and in-work poverty in an advanced industrial nation: The lived experience of multiple disadvantage in a post-financial crisis UK. (August 2019) - Richards, James; Sang, Kate
The 2007–2008 financial crisis has affected the prospects for workers in a range of ways. In-work poverty represents just one, yet key feature of how prospects for workers have changed in recent times. In-work poverty disproportionately impacts on marginalised groups, such as the disabled. Current research reveals little about how disability and poverty intersect in the context of employment. To address this oversight, life history interviews were conducted with disabled people in in-work poverty. The findings were analysed using the social model of disability and the lens of intersectionality. The results highlight how government policies, employer practices and household finances impact on disabled workers' lived experience of in-work poverty. The findings suggest that governments and employers can do more to reduce barriers to escaping in-work poverty for disabled workers.